When should we provide separate auto and truck roadways? - Robert W. Poole (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
The concept of the general purpose (GP) lane has dominated modern highway thinking and practice in OECD countries, especially for limited-access highways such as inter-city motorways and urban expressways, whether tolled or non-tolled. This paper raises the question of whether, in some circumstances, specialized lanes for light vehicles (cars, vans and pickup trucks) and heavy vehicles (generally more than two axles) might be cost-effective.
Keywords: 330